Does anti-corruption disclosure affect banking performance?. Issue 4 (1st June 2020) - Nobanee, Haitham; Atayah, Osama F.; Mertzanis, Charilaos
Abstract : Purpose: This paper aims to test the levels of anti-corruption disclosure and its implication on the banking performance of both conventional and Islamic banks listed on the Abu Dhabi Securities Exchange and Dubai Financial Market. Design/methodology/approach: The authors have used the content analysis to identify the levels of anti-corruption disclosure in the banks' annual reports. They have also used the two-steps generalized method of moments (GMM) regression applied to dynamic panel data analysis to examine the effect of the anti-corruption disclosure on the banking performance. Findings: The empirical results show that the anti-corruption disclosure is at low levels for all banks and conventional and Islamic banks samples. The results also show no significant differences in the anti-corruption disclosure between Islamic and conventional banks. The results of the two-steps GMM regression applied to dynamic panel data analysis show a negative and significant impact of the levels of anti-corruption disclosure on the bank's performance for both all banks and conventional banks; the results of the dynamic panel data analysis show an insignificant impact of anti-corruption discloser for the Islamic banks' sample. Practical implications: The findings recommended a comprehensive framework of anti-corruption disclosure to the central banks and financial market regulators to enhance anti-corruption practices within the financial institutions to increase transparency and enhance their performance. Originality/value: Fighting against anti-corruption is essential for financial institutions. This paper is the first study that examined the extent of anti-corruption levels and their effect on banking performance for both Islamic and conventional banks operates in the UAE. The findings help in enhancing reporting practices in terms of anti-corruption to improve transparency and performance in the banking sector.